Further Evidence of the Possibility of Exploiting Anticipatory Physiological Signals To Assist Implicit Intuition of Random Events - Tressoldi, Patrizio E.; Martinelli, Massimiliano; Scartezzini, Laura; Massaccesi, Stefano (Journal of Scientific Exploration, 2010)
With this study, we aimed to replicate and extend the findings obtained by Tressoldi, Martinelli, Zaccaria, and Massaccesi (2009) who showed that in participants with high scores on the Tellegen Absorption Scale (score > 20), anticipatory heart rate responses in an implicit pre-alerting paradigm could be used to improve their intuitive decisions on random events. In this study, two pools of pleasant and alerting sounds were used to test the generality of previous findings. By using fifty participants, it was also possible to study whether gender could be a further moderator of the observed effect. Results confirm the findings of Tressoldi, Martinelli, Zaccaria, and Massaccesi (2009), clarifying that the effect was present only in females. Females with a high level of absorption predict more hits than females with a low level. Further statistical analysis suggests that absorption acts as an implicit cognitive “filter” only for pleasant sounds. Keywords: anticipatory responses—heart rate—intuition—random events— absorption—gender differences